Street network analysis by spot imagery for urban morphology study: case study: Melaka - Mohd Nor, Marina; Hj. Mohd. Noor, Norzailawati; Simoda, Sadayuki (2017)
This paper is based on the study of morphological changes in Melaka, Malaysia. In order to identify the morphology of this city, the street network has been studied to determine the evolutionary of urban form and structure. The objective of this paper is to examine the movement and direction of the street pattern in influenced the morphology of the city from the year 1993 to 2016. Three series of satellite images on the year 1993, 2005 and 2015 from SPOT satellite have been used in detecting the development of street network pattern aided by remote sens-ing and GIS software. By extracting the street in 20 years of development, a com-parison of the street pattern will be taken into consideration to examine the direc-tion of the expansion of Melaka city. The finding shows that the streets expansion growth fast as the more settlement were built along this process and the expansion was merely influenced by the location of the site which near to Malacca Straits and as a port for trade sector. Further, the movement of streets expanding inwards to the inner city and along the shoreline. Finally, this study shows a street network as one of the principle elements in the urbanization process and it provides an understanding key on how cities are formed and develop in order to achieve a resilient city.